Logros en motivación y el tercer nivel de estructura del conocimiento: un estudio empírico en contextos de aprendizaje correspondientes a una modalidad híbrida ABP - Morales Bueno, Patricia (2009)
This paper reports an empirical study of achievement in motivation with an attributional perspective, and the third level of knowledge structure following Sugrue’s model, conducted with two experimental groups in which a hybrid PBL methodology was implemented, in a General Chemistry course, first year of Science and Engineering Program at the Pontificia Universidad Católica del Perú (PUCP). Both groups were compared with a control group corresponding to an equivalent course of another Peruvian university. The findings showed the significant influence of learning context on achievements in the studied variables, especially the negative effect of an inefficient group dynamics.